An overview of current and emerging diagnostic, staging and prognostic markers for prostate cancer. (2nd August 2020) - Brönimann, Stephan; Pradere, Benjamin; Karakiewicz, Pierre; Abufaraj, Mohammad; Briganti, Alberto; Shariat, Shahrokh F.
ABSTRACT: Introduction: This manuscript aims to give an overview of current diagnostic, staging, and prognostic markers for prostate cancer (PCa) and discuss emerging approaches. The widespread use of PSA for early detection led to improved survival but at the cost of over-diagnosis, often associated with over-treatment and its adverse events. There is thus an unmet need for new markers to sustainably improve the diagnosis and risk assessment, thereby providing a more accurate treatment decision for each individual patient. Areas covered: Promising new molecular serum (PSA, PHI, 4Kscore®), urine (Progensa®, SelectMDx®, MiPS) and tissue-based markers (Ki-67, Prolaris®, ConfirmMDx®, Oncotype Dx®, Decipher®, Promark®) will be discussed in this review. Expert opinion: Over-diagnosis and difficulties in prognosticating clinical outcome among patients with similar histological and clinical parameters often lead to over- or under-treatment. New markers will probably be used with clinical and histopathological features as well as imaging diagnostics to capture the comprehensive biology and clinical behavior of PCa. New biomarkers open the avenue to avoid mpMRI with targeted biopsy in the future, thereby sparing risks and pitfalls associated with this approach. Before this utopia becomes reality, the panel of technologically complementary markers need to prove that they are better, cheaper, and faster than current strategies.